Design and Implementation of a Web-Based Savings and Loan Information System - Jauharul Qalbi; Jaswadi Jaswadi; Kartika Dewi (International Journal of Information Technology and Computer Science Applications, 2026)
This study aimed to design and implement a web-based Savings and Loan Information System for Koperasi Konsumen Raudhah Amanah Bunobogu while supporting the improvement of its existing business processes. The study was motivated by operational challenges arising from manual transaction recording, fragmented data management, reporting delays, and limited access to centralized information. Data were collected through observation, interviews, and documentation studies. A Fishbone Diagram was employed to identify the root causes of operational problems, whereas Business Process Model and Notation (BPMN) was used to analyse the existing (As-Is) and proposed (To-Be) business processes. The system was developed using the Software Development Life Cycle (SDLC) Waterfall model and evaluated through Black Box Testing to verify its functional requirements. The developed system successfully integrates key cooperative operations, including member management, savings transactions, loan processing, installment payments, and financial reporting within a centralized web-based platform. The Black Box Testing results confirmed that all implemented functionalities operated in accordance with the specified system requirements. These findings demonstrate that integrating BPMN-based business process redesign with information system development provides a structured approach to supporting the digitalization of savings and loan cooperative operations. Future studies are encouraged to evaluate the organizational impact of the system through quantitative performance measurements and user-based assessments.